Family Development Index (IDF) in the municipality of Viçosa, evolution between 1980 and 2010 - Olher, Bruno Silva; Barreto, Maria de Lourdes Mattos; Braga, Gustavo Bastos; Loreto, Maria das Dores Saraiva de (Interações, 2018)
This study analyzed the situation of families in the city of Viçosa in 1980, 1991, 2000 and 2010 from a multi-dimensional perspective based on methodology adapted from that of Barros, Carvalho and Franco (2003), which was based on micro-data from the demographic census. Through the enormous amount of information contained in the database, it was possible to undertake a broad analysis enabling the household’s living conditions to be evaluated.